A Simple and Effective Strategy to Prevent Power Transformer Overloading - Bin-Halabi, Ahmed; Nouh, Adnan; Abouelela, Mohammad (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
This paper presents a novel strategy to prevent overloading of distribution transformers. The strategy is based on a developed algorithm for home energy management (HEM) system. The algorithm is mainly aimed to prevent the complete power outage of an area that may occur due to transformer overloading. The task can be accomplished by a supervised reduction in power consumption of the customers supplied through the overloaded transformer without tripping the transformer, since the complete disconnection of service is considered undesirable by the customers. The proposed algorithm is intended to minimize the number of switched-off appliances to lessen their impact on the customer's comfort level. The strategy is simple and effective in terms of cost and performance. MATLAB/Simulink was used to simulate the system and to validate the proposed strategy. The simulation results show the effectiveness of the strategy to avoid transformer overloading and thus preventing power outage.